Environmental Enrichment for Broiler Breeders: An Undeveloped Field - Riber, Anja B.; de Jong, Ingrid C.; van de Weerd, Heleen A.; Steenfeldt, Sanna (Frontiers in Veterinary Science, 2017)
Welfare problems, such as hunger, frustration, aggression, and abnormal sexual behavior, are commonly found in broiler breeder production. In order to prevent or reduce these welfare problems it has been suggested to provide stimulating enriched environments. We review the effect of the different types of environmental enrichment for broiler breeders, which have been described in the scientific literature, on behavior and welfare. Environmental enrichment is defined as an improvement of the environment of captive animals, which increases the behavioral opportunities of the animal and leads to improvements in biological function. This definition has been broadened to include practical and economic aspects as any enrichment strategy that adversely affects the health of animals (e.g. environmental hygiene), or that has too many economic or practical constraints will never be implemented on commercial farms and thus never benefit animals. Environmental enrichment for broiler breeders often has the purpose of satisfying the behavioral motivations for feeding and foraging, resting, and/or encouraging normal sexual behavior. Potentially successful enrichments for broiler breeders are elevated resting-places, cover panels, and substrate (for broiler breeders housed in cage systems). However, most of the ideas for environmental enrichment for broiler breeders need to be further developed and studied with respect to the use, the effect on behavior and welfare, and the interaction with genotype and production system. In addition, information on practical use and the economics of the production system is often lacking although it is important for application in practice.